Evaluating the Parallel Simulation of Dynamics of Electrons in Molecules on AWS Spot Instances - Munhoz, Vanderlei; Castro, Márcio; Rego, Luis G. C. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2023: Anais do XXIV Simpósio em Sistemas Computacionais de Alto Desempenho, 2023)
In this paper, we evaluate the cost-effectiveness and performance of simulating the dynamics of electrons in molecules on AWS and investigate the implications of using various types of storage solutions, contrasting the results with those obtained on a traditional HPC cluster. Our findings reveal key insights into the computational efficiency and cost-effectiveness of these diverse platforms, contributing to the critical discourse on how to optimally harness the power of modern computing infrastructures for complex molecular simulations.